Information use among first-year students in health sciences: Is an intervention needed? - Øvern, Karen Marie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
This study investigated what strategies first-year students in health sciences on three university colleges in Norway used when faced with a new written assignment. Questionnaires were distributed among health students on three campuses, and interviews with librarians at the campuses were held after initial data collection. The study showed that many students lack basic information skills, but are not aware of it themselves, that many first-year students are choosing familiar information sources like Google and text-books from their reading lists, and it showed that librarians at their institutions had experienced that many first-year students could get by with these sources. This is contrary to the intentions in evidence-based practice, and the Norwegian Qualifications Framework.The study also suggests that the lack of a Norwegian framework or standard for information literacy training is making the teaching efforts seem random and based on the librarian`s personal relationship with teachers.